EVALUASI PENERAPAN SISTEM PENGENDALIAN INTERNAL PADA KINERJA KEUANGAN DI PERGURUAN TINGGI NEGERI - Wahidah, Wahidah; Nurhazana, Nurhazana (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study aims to evaluate the implementation of the Implementation of the Internal Control System on Financial Performance at the Bengkalis State Polytechnic based on Government Regulation Number 60 of 2008 concerning the Government Internal Control System (SPIP) by looking at the SPIP elements, namely control environment, risk assessment, control activities, information and communication and monitoring of internal control. This research is descriptive qualitative. The sampling technique used purposive sampling. Data collection techniques carried out consisted of interviews, observation and documentation. The results of this study indicate that the implementation of the implementation of the internal control system on financial performance at Bengkalis State Polytechnic is in accordance with Government Regulation Number 60 of 2008. This can be proven by reliability in financial reporting and compliance with laws and regulations, so that effectiveness and efficiency are achieved in in the implementation of activities in achieving maximum output